ISOKINETIC STRENGTH IS COMPARABLE AMONG ADOLESCENT PATIENTS WHO HAD EITHER A SINGLE INJECTION FEMORAL NERVE BLOCK OR CONTINUOUS FEMORAL NERVE CATHETER DURING ANTERIOR CRUCIATE LIGAMENT RECONSTRUCTION. Issue 7 (30th July 2021) - Gagliardi, Alexia G.; Parikh, Harin B.; Mandler, Tessa N.; Kanai, Susan K.; Howell, David R.; Albright, Jay C.
Background: Single injection femoral nerve blocks or continuous femoral nerve catheters are commonly used during anterior cruciate ligament reconstruction (ACLR). However, both single injection and continuous femoral nerve catheters have been associated with decreased quadriceps strength and function up to 6 months postoperative compared to no regional anesthesia Purpose/Hypothesis: We compared isokinetic limb asymmetry 5-10 months post-surgery between patients who received either single injection or continuous femoral nerve block during ACLR. We also assessed patient characteristics potentially associated with strength deficits. We hypothesized that patients with continuous femoral nerve catheters would demonstrate decreased quadriceps function due to increased local anesthetic. Methods: We reviewed medical records of patients ages 10-19 years who completed isokinetic testing 5-10 months following quadricep tendon ACLR by a single surgeon. Patients were excluded for previous lower limb surgery. We grouped patients based on whether they received a single injection femoral nerve block (FNB group) or a continuous femoral nerve catheter (FNC group) intraoperatively. Using isokinetic data at 60, 180, and 300 degrees per second, we calculated maximum torque percent deficit of the involved compared to the uninvolved leg, as well as compared peak torque extensor and flexor deficits (% difference between operative/non-operative sides) between groups. Results: Sixty-two patients were included: 50 who received FNC and 12 who received FNB (Table 1). There were no significant differences between continuous femoral nerve block and single-shot femoral nerve block groups for extensor deficits at any speed (Figure 1) or for flexor deficits at any speed (Figure 2). At 60 degrees/s (p=0.006) and 180 degrees/s (p=0.017), longer time since surgery was associated with smaller extensor deficits (Table 2). At 180 degrees/s (p=0.008) older age was associated with greater extensor deficits (Table 2). At 60 degrees/s (p=0.017) skeletal maturity was associated with greater extensor deficits (Table 2). At all speeds, an injured dominant limb was associated with smaller flexor deficits (Table 3). Older age was associated with greater flexor deficits at 60 deg/s (Table 3). Conclusion: No apparent significant isokinetic strength differences were found between groups 5-10 months postoperatively. Longer time from surgery was significantly associated with decreased extensor deficits among both groups at slower isokinetic test speeds. Our data suggest increased isokinetic strength recovery over the 5-10-month timeframe. The surgeon, anesthesia team, and patient should choose the pain management protocol based on resource and patient factors. Tables and Figures: Figure 1. Mean values (error bars represent 95% confidence intervals) for Peak Torque (ft-lb) extensor % deficits (% change between surgically affected and unaffected sides) between continuous femoral nerve block and single-shot femoral nerve block groups at each of the isokinetic test speeds. Figure 2. Mean values (error bars represent 95% confidence intervals) for Peak Torque (ft-lb) flexor % deficits (% change between surgically affected and unaffected sides) between continuous femoral nerve block and single-shot femoral nerve block groups at each of the isokinetic test speeds.